The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1742-4755-11-68
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of men in maternal health care: cross-sectional, pilot case studies from Maligita and Kibibi, Uganda

Abstract: BackgroundThe International Conference on Population Development held in Cairo in 1994 identified the importance of male involvement in reproductive health programs. Since then, there has been an increase in reproductive health initiatives that target both men and women in an attempt to fulfill the 5th Millenium Development Goal. Yet, while the benefits of male involvement have been acknowledged, there continues to be a challenge in creating a space for and engaging men in maternal health. This is problematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 15 publications
14
86
2
7
Order By: Relevance
“…The perception of husbands as the “providers” of basic goods–food and clothes–has been reported previously [10,11], and emerged in the present study. Each focus group unanimously noted that the husband was responsible for providing his wife with food.…”
Section: Discussionsupporting
confidence: 73%
“…The perception of husbands as the “providers” of basic goods–food and clothes–has been reported previously [10,11], and emerged in the present study. Each focus group unanimously noted that the husband was responsible for providing his wife with food.…”
Section: Discussionsupporting
confidence: 73%
“…Their ignorance resulted in late antenatal booking where only 12.4% of the women came for their antenatal booking in the first trimester. This is lower as compared to findings in another study done in Ghana where 63.6% of the women interviewed admitted going for their first antenatal check up in the first trimester [16].…”
Section: Discussioncontrasting
confidence: 52%
“…The literature shows that gendered norms and expectations, in general, hinder men’s involvement in reproductive healthcare and their access to programs and services [2426]. However, there are also studies pointing out that social norms exist that may promote men’s involvement in reproductive health [2628]. Some studies in sub-Saharan Africa also revealed that men are often bound to normative social and cultural contexts fueled by gender expectations [13,2931].…”
Section: Introductionmentioning
confidence: 99%